2022
DOI: 10.1038/s41598-022-04840-9
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects of a chlorogenic acid- and cynarine-enriched fraction from Dittrichia viscosa root extract

Abstract: Dittrichia viscosa is a perennial Mediterranean plant used in traditional medicine for “calming purposes”, pointing at a possible antidepressant activity of the plant. We conducted chromatographic and bioassay-guided fractionation of D. viscosa root extract to isolate a specific fraction (fraction “K”) with antidepressant-like characteristics in vivo and strong antioxidant properties in vitro. A single dose of “K” reduced immobility time in the forced swim test with a mouse model possessing a depressive-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In fact, coffee has been shown to have antidepressant effects and though this has been attributed to caffeine, decaffeinated coffee rich in chlorogenic acid can also improve mood [56][57][58]. The antidepressant potential of chlorogenic acid is also supported by experiments in rats and mice, showing that chlorogenic acid or chlorogenic acid-rich plant extracts had anxiolytic and antidepressant effects [59][60][61][62][63]. Due to these findings and our results, we initiated studies to identify a mechanism of how chlorogenic acid may lead to resilience against stress.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, coffee has been shown to have antidepressant effects and though this has been attributed to caffeine, decaffeinated coffee rich in chlorogenic acid can also improve mood [56][57][58]. The antidepressant potential of chlorogenic acid is also supported by experiments in rats and mice, showing that chlorogenic acid or chlorogenic acid-rich plant extracts had anxiolytic and antidepressant effects [59][60][61][62][63]. Due to these findings and our results, we initiated studies to identify a mechanism of how chlorogenic acid may lead to resilience against stress.…”
Section: Discussionmentioning
confidence: 99%
“…An ultraperformance liquid chromatography-quadrupoletime-of-flight-mass spectrometry has been employed in several studies to characterize the potential components [66]. Additionally, LC-MS analysis revealed the presence of compounds like Mahaleboside (Coumarin glycosides), Chlorogenic acid (Polyphenols), Crotanecine (Pyrrolizidine alkaloids), Perlolyrine (Harmala alkaloids), Phrymarolin I (Benzodioxoles), Diplodiatoxin (Gamma keto acids), Dihydrocapsaicin (Capsaicinoid), Morindone (Anthraquinone), Corchorifatty acid (Linoleic acid), and Polyporusterone B (triterpene carboxylic acid) were known to possess anticancer, depression, hypertension, anti-inflammatory activities [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Murlanova and coworkers studied antidepressant-like activity of the root extract from D. viscosa [27]. A fractionation of the crude extract led to the identification of fractions active against H2O2induced damage in the rat pheochromocytoma (PC12) cells.…”
Section: Hydroxycinnamatesmentioning
confidence: 99%
“…Except for the cytotoxic or antiproliferative action, the preparations from the plants of the subtribe are often investigated for their anti-inflammatory [10][11][12], antidiabetic [13][14][15], antilipidemic [16][17][18], vasorelaxant/antihypertensive [19,20], anti-oxidative stress [21][22][23] and hepatoprotective [24][25][26] activities in vivo. Recently, their efficacy in the prevention of depression-like behavior in rodents has been also explored [27,28]. The results of the studies have suggested that the polyphenolic metabolites are, at least in part, responsible for the observed pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%